Sustainable Management of Urban Green Spaces in Compact Cities: Case Studies from Cairo - Ali, Nehal (AUC Knowledge Fountain, 2017)
The management of urban green spaces in developing countries is a challenging issue today. The provision of services related to the maintenance of urban green spaces is an integrated aspect of urban green space management systems. With minimal awareness provided by the local authorities and the government entities, well-managed green spaces are deprioritized compared to other basic demands of society. The standards set forth by international institutions that feed into an integrated land management systems of the urban landscapes are vastly attainable, yet Egypt still remains isolated in this topic of research. The gap between the provision of services and the overall quality and performance of a sustainable urban green space will further be investigated in this research. This research considers the factors of contribution to the mismanagement of urban green spaces adduced by the governmental agencies as well as the community based management systems by analyzing the current management conditions. The development of the framework of indicators has been extracted from the sustainable approaches of urban green spaces from the literature leading to 5 key themes: governance set up, management arrangements, resource management, participatory roles, and environmental aspects. The research aims at providing a qualitative analysis of accessing the success/failure levels of two local case studies from Cairo, in order to propose an effective management practices with a comprehensive inclusion of a participatory form of governance and shared implementation systems to enhance the social, economic, and environmental benefits of the urban landscapes in Cairo, Egypt. Thus, promoting city attractiveness, a better efficacy in managing resources, and improving the overall wellbeing of urban dwellers in compact cities. The government based management site has failed to provide successful sustainable measures in all five themes and the community based management site has failed to provide sustainable measures in two themes: resource management and management arrangements. The study proves that the lack of inclusion of social participation, and a collaborative planning and management with shared decision making processes have led to the deterioration and decay of the overall quality of urban green spaces for the government managed case study, as for the community managed case study, resources and funding were key contributors to the failure of its management sustainability.